Scoping challenges and opportunities presented by COVID-19 for the development of sustainable short food supply chains - Baptista, Nuno (2022)
Over the past decades, short food supply chains attracted government and public support owing to their potential to mitigate some of the sustainability issues associated with the conventional globalized food supply system. The recent event of the coronavirus disease pandemic placed unprecedented pressure on food supply systems worldwide, and it constitutes a unique opportunity to evaluate the performance of food chains. Through a scoping review of the academic literature, this study provides a critical assessment of the implications of the pandemic on short food supply chains in multiple economies. Following the guidelines outlined in the PRISMA-ScR framework, the SCOPUS and ISI Web of Science databases were searched for the academic literature on the topic. The results of the review indicate that, besides the direct effects of the pandemic, the indirect effects resulting from public policies implemented to contain the spread of the virus affected all relevant dimensions of sustainability. Moreover, the consequences of the pandemic were more disruptive in the short food chains of low-income countries than in those of high-income countries. The main challenges and opportunities for the sustainable development of short food supply chains are identified, and recommendations for future research are outlined.